Iterative Distributed MPC for Power Dispatching Problem in Smart Grid - Qiang, Zhiwen; Dai, Li; Xia, Yuanqing (2018 Chinese Automation Congress (CAC), 2018)
This paper considers a power dispatching problem in a smart grid, which consists of one generator and n loads and is subject to several physical constraints. To maximize the social benefit, we first develop a distributed gradient algorithm to compute the optimal stable states. Then a computationally convenient distributed model predictive control (DMPC) algorithm is proposed to stabilize the smart grid into a small neighborhood of the optimal stable states. The closed loop system is guaranteed to satisfy the constraints and achieve the social benefit maximization. Numerical examples are given to illustrate the performance of the designed schemes.